Infrastructure & Ops superstream series SRE edition - Fong-Jones, Liz (O'Reilly Media, 2020)
"This four-part series of half-day online events, hosted by chair Sam Newman, covers the most challenging and promising topics facing those working in infrastructure and operations today. Site reliability engineering (SRE) is the practice of ensuring a company's digital assets remain stable, performant, and resilient. Given that all companies rely on a digital presence these days, SRE is becoming increasingly vital to the engineering teams supporting the sites- and ultimately the business. In this edition of the O'Reilly Infrastructure & Ops Superstream Series, Liz Fong-Jones, Eric Zielinski, Jason Patterson, Debbie Wood and Randy Shoup introduce you to SRE concepts and best practices so that you can learn how to put them to work in your organization."--Resource description page